2011
DOI: 10.1002/crat.201000635
|View full text |Cite
|
Sign up to set email alerts
|

Formation of calcium phosphates by vapour diffusion in highly concentrated ionic micro‐droplets

Abstract: In this work we have used the sitting drop vapour diffusion technique, employing the "crystallization mushroom" to analyze the evolution of calcium phosphate crystallization in micro-droplets containing high initial concentrations of Ca 2+ and HPO 4 2-. The decomposition of NH 4 HCO 3 solution produces vapours of NH 3 and CO 2 which diffuse through the droplets containing an aqueous solution of Ca(CH 3 COO) 2 and (NH 4 ) 2 HPO 4 . The result is the increase of pH by means of the diffusion of NH 3 gas and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Indeed, anionic sites within the HAp crystals are very susceptible to carbon dioxide originated from the atmosphere, so that carbonate ions (CO 3 2 À ) generated from CO 2 in the reaction solution can substitute hydroxyls or phosphates in the crystal lattice and based on this substitution, type A and type B of carbonated HAp are, respectively, formed [32,33]. Although the published data in the literature has led to some contradictory explanations regarding which bands correspond to the A-, B-, or mixed AB-type carbonate substitutions, but according to the results of IR analysis recently reported [32][33][34], the nanoparticles synthesized in the present study can be corresponded to the B-or mixed AB-type carbonated structures. Table 3 specifies the carbonated specimens and provides information on the sites where the carbonate groups were substituted.…”
Section: Phase Identificationmentioning
confidence: 84%
“…Indeed, anionic sites within the HAp crystals are very susceptible to carbon dioxide originated from the atmosphere, so that carbonate ions (CO 3 2 À ) generated from CO 2 in the reaction solution can substitute hydroxyls or phosphates in the crystal lattice and based on this substitution, type A and type B of carbonated HAp are, respectively, formed [32,33]. Although the published data in the literature has led to some contradictory explanations regarding which bands correspond to the A-, B-, or mixed AB-type carbonate substitutions, but according to the results of IR analysis recently reported [32][33][34], the nanoparticles synthesized in the present study can be corresponded to the B-or mixed AB-type carbonated structures. Table 3 specifies the carbonated specimens and provides information on the sites where the carbonate groups were substituted.…”
Section: Phase Identificationmentioning
confidence: 84%
“…Numerous methods have been used for the synthesis of apatite crystals. They can be classified into the following categories: wet chemical precipitation [75][76][77], sol-gel synthesis [78][79][80], coprecipitation [24,81], hydrothermal synthesis [82][83][84], rapid or continuous precipitation from solution [85], mechanochemical synthesis [86], microwave processing [87][88][89][90], vapor diffusion [91][92][93], silica gel template [94], emulsion-based syntheses [95], electrospraying [96], electrospinning [97], flux cooling [98] and other methodologies producing (nano)crystals of various shapes and sizes [99,100]. Dorozhkin [5] has recently produced a review of those methods producing nanocrystalline apatites and has underlined that the interest for nanocrystalline apatites was quite recent.…”
Section: Crystallization Methods Of Apatitesmentioning
confidence: 99%
“…It has been reported that Ca/P atomic ratios varying between 1.4 and 2.4 are often observed for hydroxyapatite prepared from solution co‐precipitation . Similarly, the additional carbon signal in the samples is most likely a result of carbonate impurities . Further investigation into preparation induced impurities should be performed in future studies.…”
Section: Discussionmentioning
confidence: 95%